Evaluation of Sympathetic Nerve Function Status in Hypertensive Patients (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Hypertension is independent and the most powerful predictor of cardiovascular morbidity and mortality. Sympathetic overdrive may be related to essential hypertension. Heart Rate Variability (HRV) analysis is one of the most quantitative markers of autonomic activity in hypertensive patients.Objective: To assess the cardiac autonomic nerve function status by heart rate variability in essential hypertension.Materials and Methods: This cross sectional study was carried out to observe the HRV in 60 hypertensive male patients with age ranging from 40-60 years (group B) in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from 1st July 2008 to 30th June 2009. Based on treatment, hypertensive patients were divided into B1 (untreated patients on their 1st day of diagnosis) and B2 (patients with antihypertensive therapy for less than 5 years). For comparison, 30 apparently healthy normotensive subjects (group A) matched by age sex were also studied. The study group was selected from the Out Patient Department of Cardiology, BSMMU, Dhaka and the control group was selected by personal contact. Heart Rate Variability parameters were assessed by Polygraph (RMS Polyrite D, version2.2) and for statistical analysis Independent sample t-test, One-way ANOVA test, Chi-square test and Pearson’s correlation coefficient tests were done as applicable.Results: LF/HF(Low Frequency/High Frequency) ratio and LF norm (normalized unit) were significantly (p